The Use of Learning Videos to Motivate Elementary School Students to Learn Football Game Materials - Rohman, Arifur; La Kamadi; Sofyan Haeruddin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
This study tries to ascertain whether using video in the classroom can boost students' motivation to learn about soccer game content. This kind of study employs classroom action research with a subject population of 78 students in class VI at MI Salafiyah Sempu during the odd semester of the 2021–2022 academic year. A questionnaire and observational methods are employed to obtain the data. Quantitative descriptive data analysis is the method of data analysis that is used. The average class student's learning motivation increased as a result of the processing of the research data, rising from 76.82 percent in the first cycle to 90.16 percent in the second, and meeting the study's success threshold of 80 percent. Based on the study's findings, it was determined that using video to teach seventh-grade students at MI Salafiyah Sempu about soccer in the odd semester of the 2021–2022 academic year may boost their enthusiasm to learn. Therefore, as a suggestion that the use of video learning can increase student motivation.